Best Policy Practices for Promoting Energy Efficiency - Nations Unies (United Nations, 2015)
This publication is prepared in the framework of the United Nations Development Account project “Promoting Energy Efficiency Investments for Climate Change Mitigation and Sustainable Development”, which is implemented jointly by all five UN Regional Commissions with UNECE as the lead agency. This publication highlights the best policy practices for promoting energy efficiency in UNECE region and beyond. The objective of the publication is to present a structured framework of policies and measures to promote energy efficiency investments for climate change mitigation and sustainable development, as well as to develop a menu of energy efficiency policies and measures. Governments, business community, experts, project developers, and other stakeholders will find this publication to be a useful companion for understanding and applying the best policy practices in improving energy efficiency.